2012
DOI: 10.1002/ajim.22024
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of acute occupational pesticide poisoning among male farmers in South Korea

Abstract: Our nationwide sampling survey demonstrated that acute occupational pesticide poisonings are highly prevalent among male South Korean farmers. Intensive intervention efforts to reduce occupational pesticide poisoning are urgently needed in South Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 23 publications
3
22
0
1
Order By: Relevance
“…In South Korea, an elevated occupational pesticide poisoning incidence of 24.7 per 100 population among male agricultural workers has been reported using nationwide survey data [29], and the incidence was significantly related with work-related factors such as poor personal hygiene practices and failure to make use of personal protective equipment [30]. Average pesticide application by unit of agricultural land in South Korea is also much higher than in other developed countries [31].…”
Section: Discussionmentioning
confidence: 99%
“…In South Korea, an elevated occupational pesticide poisoning incidence of 24.7 per 100 population among male agricultural workers has been reported using nationwide survey data [29], and the incidence was significantly related with work-related factors such as poor personal hygiene practices and failure to make use of personal protective equipment [30]. Average pesticide application by unit of agricultural land in South Korea is also much higher than in other developed countries [31].…”
Section: Discussionmentioning
confidence: 99%
“…The details of this study design and population have been described previously [7]. In brief, a nationwide sampling survey of male farmers in South Korea was conducted in 2011 using stratified multistage probability sampling methods and adopting in-person interviews with selected households from the 2010 Korean Agricultural Household registry data.…”
Section: Methodsmentioning
confidence: 99%
“…Previous field studies from Nicaragua [2], Indonesia [3], Vietnam [4], Brazil [5], and China [6] have reported an occupational pesticide poisoning prevalence of 8.8% to 31%, based on self-reporting, although the study period and definition of poisoning varies between studies. In South Korea, a recent nationwide sampling survey conducted in 2011 demonstrated that the incidence rate of acute occupational pesticide poisoning was 24.7 per 100 male farmers, which corresponds to 209,512 cases in 2010 [7]. …”
Section: Introductionmentioning
confidence: 99%
“…The details of this study design and population have been previously described 12. In brief, a nationwide sampling survey of male farmers residing in rural areas in South Korea was conducted during February and March of 2011.…”
Section: Methodsmentioning
confidence: 99%